Degradation of the viral strand of phiX174 parental replicative-form DNA in a rep- host. - Bowman, K L (1975)
A progressive degradation of the parental viral strand label is observed upon infection of a Rep- mutant of Escherichia coli by 32P-labeled phiX174. Very little parental label remains in the RF (replicative form) by 47 min after infection. Concomitant with this degradation, replicative intermediates are formed which sediment at 21s, the rate of RF I (supercoiled-closed circular DNA), in a neutral sucrose gradient but which denature and sediment in alkaline gradients as single strands of unit size and larger. These denaturable 21s replicative intermediates have been shown previously to be RF molecules containing an elongated viral strand. Addition of chloramphenicol at 7 min after infection at 30 mug/ml, a concentration sufficient to block RF leads to SS (single strand) synthesis but not RF leads to RF synthesis in a wild-type host cell, reduced the amount of viral strand elongation but did not prevent viral strand degradation. The addition of chloramphenicol at 150 mug/ml at 7 min after infection totally prevents both the degradation of the parental label and the formation of the replicative intermediates with elongated tails. We infer that degradation of the viral strand requires the gene A-mediated nicking of the viral strand but not the concomitant elongation of the viral strand.